Clinical Spectrum, Therapeutic Options, and Outcome of Advanced Heart Failure in Hypertrophic Cardiomyopathy. (November 2015) - Pasqualucci, Daniele; Fornaro, Alessandra; Castelli, Gabriele; Rossi, Alessandra; Arretini, Anna; Chiriatti, Chiara; Targetti, Mattia; Girolami, Francesca; Corda, Marco; Orrù, Pierpaolo; Matta, Gildo; Stefàno, Pierluigi; et al.
Abstract : Background—: The clinical course of patients with hypertrophic cardiomyopathy and advanced heart failure (HF) subtended by progressive left ventricular dysfunction has received limited attention. Our aim was to assess the outcome of HF and impact of treatment options including the implantable cardioverter-defibrillator and heart transplantation (HT) in patients with hypertrophic cardiomyopathy evaluated at 2 Italian referral centers >3 decades. Methods and Results—: All-cause mortality and a combined end point including death, HT, or appropriate implantable cardioverter-defibrillator shock were assessed in 71 consecutive patients with HF not related to outflow obstruction (7% of the entire hypertrophic cardiomyopathy cohort) followed up for 6.1±6.9 years after development of New York Heart Association class III to IV symptoms. At enrollment, left ventricular ejection fraction was <50% in 55 patients and >50% in 16; all had restrictive left ventricular filling. During follow-up, 35 patients died (49%%; 5-year rate, 49%) and 53 met the combined end point (75%; 5-year rate, 62%). Most events occurred in the 3 years after HF onset (17% per year compared with only 3% per year subsequently). Appropriate implantable cardioverter-defibrillator shocks occurred in 11 of 34 implanted patients. Of 37 patients evaluated for HT, 14 were transplanted, 10 listed, and 13 excluded; 2 early post-HT deaths occurred in patients with elevated pulmonary vascular resistance. Eleven of the 14 HT patients were alive at 10±8 years. Conclusions—: In hypertrophic cardiomyopathy, advanced HF not associated with outflow obstruction portends a severely unfavorable prognosis, particularly in the first 3 years after onset of symptoms, despite frequently preserved systolic function in about one quarter of the patients. Outcome of HT is favorable but requires early consideration, as the window of opportunity may be short. Abstract : Supplemental Digital Content is available in the text.